2019
DOI: 10.1002/pro.3586
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new strategies for grafting binding peptides onto protein loops using a consensus‐designed tetratricopeptide repeat scaffold

Abstract: Peptide display approaches, in which peptide epitopes of known binding activities are grafted onto stable protein scaffolds, have been developed to constrain the peptide in its bioactive conformation and to enhance its stability. However, peptide grafting can be a lengthy process requiring extensive computational modeling and/or optimisation by directed evolution techniques. In this study, we show that ultra-stable consensus-designed tetratricopeptide repeat (CTPR) proteins are amenable to the grafting of pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Our condence in the broad applicability of the scaffold to the display of diverse SLiMs arises from the nding that we could effectively gra two SLiMs with very different binding conformations onto the CTPR loops. The Keap1-binding peptide from Nrf2 adopts a tight turn-like conformation, 33 whereas the TBP in this work binds to ARC domains in a highly extended conformation. 36,55 It might appear that a limiting factor in this multivalent platform would be the potential for steric clashes between target and scaffold as well as between targets in a multivalent display.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Our condence in the broad applicability of the scaffold to the display of diverse SLiMs arises from the nding that we could effectively gra two SLiMs with very different binding conformations onto the CTPR loops. The Keap1-binding peptide from Nrf2 adopts a tight turn-like conformation, 33 whereas the TBP in this work binds to ARC domains in a highly extended conformation. 36,55 It might appear that a limiting factor in this multivalent platform would be the potential for steric clashes between target and scaffold as well as between targets in a multivalent display.…”
Section: Discussionmentioning
confidence: 85%
“…accommodate peptide extensions in the loop between adjacent repeats up to as many as 25 amino acids without compromising the native structure. 32,33 We then demonstrated that we could gra a SLiM from the protein Nrf2 that recognises the oncogenic protein Keap1 onto the scaffold and that we could not only recapitulate the native binding affinity but also improve it without need of sophisticated computational modelling. Thus, by combining this modular scaffold with SLiM graing we potentially have the capacity for diverse functionalization.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…As it has been known that heteromeric protein-protein interactions are often mediated by loops 33,34 , a loop-grafting can be a promising way to transfer PPI onto unrelated proteins. However, only a limited number of special proteins are reported so far to be capable of presenting PPI-mediating loop peptides in an intact binding-competent conformation, and the grafting sites are also limited [35][36][37] . Choosing appropriate loop peptide moieties is also challenging, because exible peptide conformation in isolation (i.e., detached from the target) is di cult to predict, and they tend to exhibit low a nity due to the entropic penalty upon binding 34 .…”
Section: Discussionmentioning
confidence: 99%